Acupuncture for diabetic nephropathy: mechanisms, clinical evidence, and future perspectives - Yue, Jing; Guo, Jinhao; Wang, Xinru; Kong, Yifan; Song, Lingwei; Liu, Yuanxiang; Liu, Yipeng; Yang, Ji-Guo (Frontiers in Endocrinology, 2025)
Diabetic nephropathy (DN) remains a leading cause of end-stage renal disease despite guideline-based therapy. Acupuncture has been explored as an adjunct or alternative approach. We reviewed preclinical and clinical studies (2010–2025) on acupuncture for DN, summarizing mechanisms, intervention models (acupuncture alone; with Chinese medicine; with Western medicine; triple therapy), renal outcomes, and safety. Across animal and human data, acupuncture modulates immune–inflammatory and metabolic pathways—including HMGB1/NLRP3/NF-κB, SIRT1/AMPK/PGC-1α, eNOS–NO–cGMP, and autophagy (ULK1–Beclin-1–LC3)—enhances antioxidant defenses (SOD↑, MDA/8-OHdG↓), protects podocytes, and improves microcirculation. Clinically, it is associated with reductions in proteinuria (24-h UP, UACR/UAER), improvements in renal function (Scr, BUN, eGFR), and better metabolic control and symptoms. Combined regimens (with Chinese or Western medicines) tend to yield faster or broader benefits, with no serious adverse events reported in the included studies. Evidence quality is limited by small sample sizes, single-center designs, short follow-up, heterogeneous endpoints, and incomplete safety reporting. Acupuncture shows multi-target, complementary effects for DN and may be integrated with standard care. High-quality, multicenter randomized controlled trials with standardized endpoints (e.g., proteinuria, eGFR slope), robust safety monitoring, and embedded mechanistic assessments are warranted.